Restoration in soil and plant properties in landslide damaged forest ecosystem - Mandal, Tej Narayan (Nepalese Journal of Biosciences, 2013)
The pattern of natural restoration in soil and plant components was studied in five landslide-damaged (1-58-year-old) sites in the tropical moist sal (Shorea robusta) forest ecosystem of Nepal Himalaya .Rate of restoration in soil properties was faster in the early successional stages (1-15 year) than late stages while plant biomass recovered rapidly after 15-year age. Based on the recovery in ecosystem properties; the 58- year-old landslide damaged site demonstrated the re-establishment of an ecosystem showing closer affinity with the mature sal forest. On the basis of best fit power function models it was concluded that the estimated times for the 58-year old site to reach the level of undisturbed matured sal forest would be about 30-35 years for microbial biomass (C and N) and plant biomass and about 100-150 year for soil organic Carbon and total N. Higher accumulation of soil microbial biomass, plant biomass and high N-mineralization rate at late successional stages indicated the re-establishment of an ecosystem with enriched soil and restitution of nutrient cycling during the course of ecosystem restoration DOI: http://dx.doi.org/10.3126/njbs.v2i0.7488 Nepalese Journal of Biosciences 2 : 40-45 (2012)